Adverse life events in the general population - a validation of the cumulative lifetime adversity measure. Issue 1 (31st December 2020) - Carstensen, Tina Birgitte Wisbech; Ørnbøl, Eva; Fink, Per; Jørgensen, Torben; Dantoft, Thomas Meinertz; Madsen, Anja Lykke; Buhmann, Cæcilie Christine Böck; Eplov, Lene Falgaard; Frostholm, Lisbeth
ABSTRACT: Background : Negative life events are a predictor for mental illness. However, most research has focused on selected domains, e.g. childhood or recent adversity. The Cumulative Lifetime Adversity Measure (CLAM), a newly introduced questionnaire not yet validated, examines cumulative effect of a range of events including number of exposure to the same event. This measure gives opportunity to collect detailed data on lifetime adversity in large cohort studies. Objective : The aim of this study was translation of the CLAM into Danish and validation of the CLAM in a large general population cohort. Secondly, we aimed to describe the occurrence of adverse life events in a large representative sample of the general population in Denmark. Methods : Translation and validation followed the COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) for formative models. Content and construct validity were evaluated including hypothesis testing of accumulated lifetime adversity having a U-shaped pattern with low levels of cumulated lifetime adversity as opposed to no or high levels being associated with lower emotional distress, functional impairment, and pain impairment. The field testing sample was the DanFunD cohort (n = 7493) randomly drawn in a Danish population and examined between 2012 and 2015. Results : Pilot interviews showed that the questions were confronting but not offensive, straight forward, and easy to answer. Acceptability was good. U-shaped patterns between accumulated lifetime adversity and the outcome measures were found. Quadratic term: Emotional distress (β(95%CI) 0.007(0.002;0.012), p < 0.007), functional impairment (β(95%CI) −0.002(−0.003;−0.001), p < 0.001), and pain impairment (β(95%CI) 0.004(0.002;0.006), p = 0.001). Field testing provided basic numbers for adverse life events for the Danish general population, with a cumulated lifetime adversity mean (SD), 5.9 (3.7). Compared to the US there were lower rates of violence, social/environmental stress, and disaster. Conclusions : The results from the original version were replicated, indicating high construct validity. Furthermore, content validity was good.